2002
DOI: 10.1017/s1431927601020037
|View full text |Cite
|
Sign up to set email alerts
|

The Canalicular Structure of Compact Bone in the Rat at Different Ages

Abstract: Osteocytes communicate through a canalicular system that maintains the vitality and mineral metabolism of bone. Casting the vascular canals and canaliculi of compact bone with methacrylate and viewing them with scanning electron microscopy shows their extent and relationships. Confocal laser scanning microscopy of the same specimen before corrosion establishes the degree of calcification of the different tissue components. These methods were used to compare basal with alveolar compact bone in the rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 1 publication
1
35
0
2
Order By: Relevance
“…In the same study, Vashishth and colleagues noted that ageing bone tissue is characterised by increased heterogeneity in the spatial organisation of osteocytes. A 3D study of rat bone at different ages using resin casting of the LCN and subsequent SEM and CLSM demonstrated that the internal structure of compact bone changes with age (Okada et al, 2002). Mandibles of juvenile rats had round lacunae with short, thick canaliculi, while adults had flatter, more ellipsoidal lacunae with more canaliculi, which were branched to a greater extent.…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations
“…In the same study, Vashishth and colleagues noted that ageing bone tissue is characterised by increased heterogeneity in the spatial organisation of osteocytes. A 3D study of rat bone at different ages using resin casting of the LCN and subsequent SEM and CLSM demonstrated that the internal structure of compact bone changes with age (Okada et al, 2002). Mandibles of juvenile rats had round lacunae with short, thick canaliculi, while adults had flatter, more ellipsoidal lacunae with more canaliculi, which were branched to a greater extent.…”
Section: Agementioning
confidence: 99%
“…Studies in rats found that treatment of osteoporotic animals with sclerostin antibody produced marked increases in bone formation, reversing the osteoporotic changes induced by ovariectomy (Li et al, 2009;Ominsky et al, 2014). In contrast to most other therapeutic treatments, which involve anti-resorptive agents and prevent or decelerate further bone loss, sclerostin has the potential to restore lost bone mass and strength.…”
Section: Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…The Lacuno-canalicular network is the finest network in the cortical bone tissue which orientation and morphology depends on the species, age, anatomical location on the same bone, and arrangement of collagen fibres in the bone matrix and on effects of mechanical loads (Schneider et al 2010). For example, it was found that the density of lacunae was reduced in older rats while the number of canaliculi increased and they became more properly organized (Okada et al 2002). Some data have been reported regarding lacuno-canalicular geometry; we present some of these data below.…”
Section: Lacuno-canalicular Networkmentioning
confidence: 99%